2019
DOI: 10.1007/s42452-019-0790-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of high early strength in concrete incorporating alccofine and non-chloride accelerator

Abstract: Rapid repair and retrofit of existing infrastructures demand durable high early strength materials that not only deliver sufficient strength within a short time after placement but also significantly prolong the maintenance interval. This research paper presents the effects on the mechanical properties and durability of alccofine concrete of the addition of calcium nitrate as a non-chloride hardening accelerator (NCHA). Non-chloride accelerator with concentrations of 0.65%, 0.85% and 1.05% by weight of cement,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 26 publications
2
8
0
1
Order By: Relevance
“…The compressive strength test was carried out on the standard size specimen cubes in water binder ratio as 0.45 and 0.5. From the results it is found that the maximum compressive strength of concrete is achieved by using Alccofine 10% and Fly Ash 30% [12]. The compressive strength of concrete with blend containing 59% Cement 15% Metakaolin and 26% Alccofine has achieved maximum packing density and also the flexural strength of the beam has increased with the increases in the percentage of Alccofine [13].…”
Section: -Introductionmentioning
confidence: 91%
“…The compressive strength test was carried out on the standard size specimen cubes in water binder ratio as 0.45 and 0.5. From the results it is found that the maximum compressive strength of concrete is achieved by using Alccofine 10% and Fly Ash 30% [12]. The compressive strength of concrete with blend containing 59% Cement 15% Metakaolin and 26% Alccofine has achieved maximum packing density and also the flexural strength of the beam has increased with the increases in the percentage of Alccofine [13].…”
Section: -Introductionmentioning
confidence: 91%
“…The strength enhancement was more with metakaolin in concrete compared to illuminate sludge and glass bottle powder at 7, 14 and 28 days for M30 grade of concrete. The CS of concrete was increased by filling of micropores with metakaolin, glass bottle powder and illuminate sludge powder at an early and later age [18][19][20].…”
Section: Compressive Strengthmentioning
confidence: 99%
“…The material is now being used in a number of major public and private projects. Alccofine has been studied by a number of researchers (6) and (7) who have found it to be an effective pozzolanic substance. Alccofine was found to increase concrete qualities, including resistance to acidic environments, sulfate attack, and chloride ion penetration (8) .…”
Section: Introductionmentioning
confidence: 99%